Acute Retrograde Tibiotalocalcaneal Nailing for Osteoporotic Ankle Fractures in Fragile Patients. Issue 4 (16th October 2019) - Herrera-Perez, Mario; Tejero-Garcia, Sergio; Valderrabano, Victor
Category: Ankle, Trauma Introduction/Purpose: With the rising aging of the population, osteoporotic ankle fractures represent a frequent scenario in daily practice. The coexistence of comorbidities such as poorly controlled diabetes mellitus, vascular insufficiency, and poor condition of the surrounded soft tissues, means that conventional open reduction and internal fixation methods often fail. On the other hand, conservative or orthopaedic treatments in such population are badly tolerated. Our study aims to study the short- term outcome of retrograde tibiotalocalcaneal (TTC) nailing in a selected series of fragile patients. Methods: This study included 15 patients who underwent primary retrograde TTC nailing from January 2016 to July 2018. The mean age of the patients was 83, 5 years (range, 75 to 88), and the mean follow-up period was 11, 5 months (range, 6 to 24 months) with no patient lost to follow-up. All patients but one were diabetic; 2 were non-ambulatory; and 13 walked with walking aids. The authors implemented a primary nailing without addressing tibiotalar or subtalar joint and without using a tourniquet. Complete weight bearing was allowed early as tolerated. Alignment and healing of the fracture were evaluated. American Orthopaedic Foot & Ankle Society (AOFAS) hindfoot score were recorded preoperatively and at the final follow-up. Results: One of the patients died 8 months after the treatment. Radiographic healing of the fractures were identified in 100% of the cases. In 2 cases, a complete arthrodesis of the ankle joint was achieved by simple nail reaming (Figure 1). No infection or any scarring problems was recorded. Of the 13 patients who walked with difficulty, 4 remained prostrate to a wheelchair, but the rest maintained their previous autonomy. The mean AOFAS score improved from 48 (range, 14 to 71) preoperatively to 71 (range, 44 to 81) postoperatively. Conclusion: In the view of these results, we suggest that primary retrograde TTC nailing is a valid option in selected patients with fragility ankle fractures, high comorbidity, poor condition of the soft tissues and with difficulties to walk before the fracture. This option allows an early full weight bearing, avoids complications due to joint off-loading, and achieves acceptable functional results.